Оптимизация нейрохирургических доступов с использованием цифрового атласа внутримозговых структур - Аврунин, Олег Григорьевич; Тымкович, М. Ю. (НТУ "ХПИ", 2015)
В работе рассматриваются вопросы, которые касаются возможности использования цифровых атласов внутримозговых структур в системах предоперационного планирования нейрохирургических вмешательств. В работе, в качестве такого атласа используется оцифрованный атлас Талайраха, который содержится в объеме 141x172x110. Для учета нечеткости в точном сопоставлении внутримозговых структур предложено использование модифицированного метода по расчету инвазивности хирургического доступа. При этом используется измененная версия цифрового атласа, которая получена путем размытия бинарных данных на разных рисковых модальностях. Также показан расчет риска хирургического доступа на используемом атласе.

Stereotactic brain surgery is the main method used in minimally invasive neurosurgery, especially in biopsy destruction or stimulation of deep brain structures. In combination with a variety of research methods such as tomography, stereotaxis effectively determines the trajectory of surgical approach and makes minimally invasive interventions. The aim of this paper is to examine the principles of the use of atlases of intracerebral structures with regard to the planning system. Namely, when calculating the risk of the surgery. The work deals with issues that relate to the possibility of using the digital brain atlas in neurosurgical systems of preoperative planning. In this paper, used digitized Talairach atlas stored in the volume of 141x172x110. Talairach atlas is one of the most used atlases in stereotactic procedures. To account for the fuzziness of intracerebral structures proposed the use of a modified method for the calculation of invasiveness of surgical access. It uses a modified version of a digital atlas, which is obtained by fuzzification of the binary data in different modalities risk. Blur simulates the ambiguity of the position of the intracerebral brain structures. Also showed the calculation of the risk of surgical access based on fuzzified digital atlas. The next step is the calculation of the standard surgical approaches of risk maps based on the atlas in relation to access to typical intracerebral structures. This should allow the identification of the most appropriate surgical access and demonstrate their low invasiveness. Outlook of work are the inclusion of the method in neurosurgical system of preoperative planning of surgical intervention on the human brain. This should reduce the risk of surgical intervention, and therefore increase the length and quality of life of patients.
Optimization of neurosurgical access using the digital atlas of intracerebral structures
Keywords: нейрохирургия; атлас мозга; атлас Талайраха; стереотаксис; компьютерное планирование; brain atlas; Talairach atlas; stereotaxy; computer aided planning; neurosurgery